"Everyone in Our Community Should be Informed About the Human Papillomavirus Vaccine": Latinx Mothers' Suggested Strategies to Promote the Human Papillomavirus Vaccine. Issue 5 (June 2022) - Lindsay, Ana Cristina; Delgado, Denisse; Valdez, Madelyne J.; Restrepo, Emily; Granberry, Phillip
Purpose: Parents play a critical decision-making role in vaccinating their children against human papillomavirus (HPV), and mothers, in particular, are key stakeholders as they are often the parent taking their children to healthcare visits. Given the importance of the HPV vaccination as a cancer prevention strategy, this study was designed to explore Latinx mothers' suggested strategies to promote vaccine uptake among Latinx parents. Setting and Participants: Community-based in Massachusetts, United States, and Latinx mothers. Design and Methods: Descriptive qualitative research employing individual semi-structured interviews. Data were analyzed using a hybrid method of thematic analysis incorporating deductive and inductive approaches. Results: Twenty-two, majority foreign-born (91%) Latinx mothers of adolescent girls (∼60%) and boys (∼40%) aged 11–19 years participated. Mothers suggested several strategies to promote uptake of the HPV vaccine among Latinx families including healthcare providers' increased communication and anticipatory guidance addressing factors influencing parents' HPV vaccination hesitancy, and improved community-wide dissemination of culturally and linguistically relevant information targeting not only parents of age-eligible participants but the broader community. Finally, mothers suggested the use of social media using personal narratives and an enhanced active role of schools in providing accurate information to raise awareness and educate adolescents and parents about the importance of HPV vaccination. Conclusion: Findings are relevant to the development of tailored interventions to meet the needs of Latinx populations, and ultimately increase Latinx children's HPV vaccination rates.